A, Adolescent The Relations between Parenting Styles with Adolescent Reproductive Health Knowledge in Junior High School “X” in Gianyar Regency - Pertiwi, Putu Dewi Diah; Sanjiwani, Ida Arimurti; Suarningsih, Ni Kadek Ayu (Journal of A Sustainable Global South; Vol 6 No 2 (2022): August 2022DO - 10.24843/jsgs.2022.v06.i02.p03, 2022)
Adolescence are changes both physically and psychologically. The occurrence of physical changes characterized by changes in reproductive functions and systems causes sexual motivation that makes adolescents vulnerable to diseases and reproductive health problems. Adolescents are expected to have good reproductive health knowledge to avoid various reproductive health problems. Knowledge of reproductive health is influenced by several factors, such as parenting styles. Parents have a big role in providing supervision and nurturing of teenagers in a family environment. This study aims to determine the relations between parenting styles and adolescent reproductive health knowledge. This research was conducted on April - May 2019. This research was cross sectional approach. Respondents numbered are 198 adolescents, obtained through proportional random sampling techniques. Parenting styles and health reproduction knowledge were measured using a questionnaire which has been tested for validity and reliability. Data analysis using chi-square test. The results showed there is a relationship between parenting styles and adolescent reproductive health knowledge (p <0.05). The parenting styles are necessary in providing about reproductive health knowledge to provide information by providing correct information from reliable sources.